2021
DOI: 10.3390/biomedicines9080909
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Adrenocortical Carcinoma: Current Highlights

Abstract: Introduction: Adrenocortical carcinoma (ACC) is a rare tumor, often discovered at an advanced stage and associated with poor prognosis. Treatment is guided by staging according to the European Network for the Study of Adrenal Tumors (ENSAT) classification. Surgery is the treatment of choice for ACC. The aim of this review is to provide a complete overview on surgical approaches and management of adrenocortical carcinoma. Methods: This comprehensive review has been carried out according to the PRISMA statement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…An earlier study reported lower 30-day mortality (0.5%) post-laparoscopic adrenalectomy ( 35 ). A recent systematic review ( 36 ) including 17 studies showed that although open surgery is the gold standard approach, there were no significant differences observed in the rate and time to recurrence and cancer-specific mortality between laparoscopic and open approaches (especially for tumor stage I-II). Although the robotic approach has several advantages compared to the laparoscopic, the specific indications of robotic approach in adrenal carcinoma remain unclear ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study reported lower 30-day mortality (0.5%) post-laparoscopic adrenalectomy ( 35 ). A recent systematic review ( 36 ) including 17 studies showed that although open surgery is the gold standard approach, there were no significant differences observed in the rate and time to recurrence and cancer-specific mortality between laparoscopic and open approaches (especially for tumor stage I-II). Although the robotic approach has several advantages compared to the laparoscopic, the specific indications of robotic approach in adrenal carcinoma remain unclear ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review ( 36 ) including 17 studies showed that although open surgery is the gold standard approach, there were no significant differences observed in the rate and time to recurrence and cancer-specific mortality between laparoscopic and open approaches (especially for tumor stage I-II). Although the robotic approach has several advantages compared to the laparoscopic, the specific indications of robotic approach in adrenal carcinoma remain unclear ( 36 ). The perioperative safety was found to be similar in the laparoscopic and robotic approaches; however, the hospital length of stay was better in the robotic group in a meta-analysis of 21 studies ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses were performed on limited and heterogeneous data and led to conflicting conclusions on this debated issue [ 3 , 20 , 23 , 24 , 25 ]. The recently published guidelines on the management of ACC confirmed OA as the gold standard approach; however, they considered LA as acceptable in tumors smaller than 6 cm without any evidence of local invasion [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the only chance for a cure in case of an adrenocortical carcinoma is a complete primary tumor resection, with no tumor capsule rupture or spillage of tumor cells, it is recommended to perform an en bloc resection of the adremal tumor with the peritumoral/periadrenal retroperitoneal fat. Although open adrenalectomy is the standard of surgical care [ 43 ], in patients with ACC stage I-II, there are no significant differences in terms of overall recurrence rate, time to recurrence, and cancer-specific mortality between the open and laparoscopic approaches [ 45 ].…”
Section: Potentially Malignant Adrenal Massmentioning
confidence: 99%